The effects of eight weeks of sand-based plyometric training on lower-extremity explosive strength, balance, and agility in male collegiate badminton players - Deng, Nijiao; Zheng, Xin; Wang, Hairong; Zhao, Ziren; Xia, Xu; Zhang, Hangshuo; Zhou, Kaixiang; Zhang, Bin (Frontiers in Physiology, 2025)
BackgroundBadminton is a high-intensity sport that demands explosive strength, dynamic balance, and agility. Plyometric training (PT) is crucial for enhancing these abilities, yet there is limited research comparing sand-based PT to hard-surface PT in badminton players.ObjectiveThis study compared the effects of sand-based PT and hard-surface PT on lower-extremity explosive strength, dynamic balance, and agility in male badminton players.MethodsTwenty-eight male collegiate badminton players were randomly assigned to a sand-based PT group (n = 14) or a hard-surface PT group (n = 14). Both groups performed plyometric programs twice weekly for 8 weeks. Outcomes measurement before and after training included countermovement jump (CMJ) height, squat jump (SJ) height, drop jump (DJ) height, standing long jump (SLJ) distance, Y-balance test (YBT), hexagon jump test, and badminton-specific agility test (lateral agility test and four-corner agility test). We used two-way repeated measures analysis of variance (ANOVA) (time × group) with Bonferroni post hoc tests, and effect sizes were reported as partial eta squared (ηp2) or Cohen’s d (p < 0.05).ResultsStatistical analysis revealed significant time main effects across multiple metrics: CMJ height (F = 81.26, p < 0.01, ηp2 = 0.75), SJ height (F = 82.86, p < 0.01, ηp2 = 0.76), DJ height (F = 54.58, p < 0.01, ηp2 = 0.68, large effect), SLJ distance (F = 49.86, p < 0.01, ηp2 = 0.66), dynamic balance ability (p < 0.01), and agility (p < 0.01), no significant between-group differences were found for any of the variables (p > 0.05). Additionally, a significant interaction effect between time and group was observed in the left leg to right (F = 4.76, p = 0.04).ConclusionThis study indicates that both sand-based PT and hard-surface PT over 8 weeks significantly enhance explosive power, dynamic balance, and agility performance, with no significant differences between groups.